Optimization of the Factors Priority Impact Model on the Quality of Post-Press Processes - Kudriashova, A. V.; Petryk, V. A. (Visnyk of Vinnytsia Politechnical Institute, 2024)
The paper has analyzed main post-printing operations of book processing. A set of criteria indirectly influencing the quality of post-press process execution is considered : manufacturing of booklets (including collation of printed sheets, trimming, folding, addition of supplementary elements), binding (options such as unstitched adhesive binding, sewing- adhesive binding, thread sewing, wire stitching), assembly (inserting for small-volume publications, assembly for publications exceeding 80 pages), cover materials (including four types of covers and five types of bindings), treatment of book blocks (ensuring the appropriate block format, enhancing strength, durability, and attractiveness to readers through a series of operations, the combination of which depends on the characteristics of book block binding), embellishment (providing additional decorative elements to the book through embossing, varnishing, bronzing, die-cutting, etc.), final processing (including finishing operations such as pressing the book production, applying dust jackets, packaging), and project management (formulating a clear plan for post-press process execution). The description and demonstration of the connections between factors influencing the quality of post-press processes are provided. A pairwise comparison matrix of factors using the Saaty scale of relative importance of objects is formed. For convenience, the pairwise comparison matrix is presented in tabular form. We determine and normalize the principal eigenvector of the pairwise comparison matrix. The components of the normalized vector of the matrix correspond to the weighted values of the factors of the investigated technological process. To verify the consistency of the results and the adequacy of the solution, we calculate the maximum eigenvalue of the pairwise comparison matrix, the consistency index, and the consistency ratio. Model of priority impact of factors on the quality of post-press processes execution, where the highest priority belongs to the "project" factor, i.e., the factor with the highest weighted value has been developed.